THE USE OF DEMPSTER SHAFER'S METHOD FOR DIAGNOSING ACUTE RENAL FAILURE IN CHILDREN - Nopita, Siska; Simanjuntak, Magdalena; Lubis, Imran (Yayasan Bina Internusa Mabarindo, 2023)
Acute kidney failure (acute kidney injury) is a condition in which the kidneys stop functioning suddenly. Acute kidney failure is known to attack children in the age range of 6 months-18 years, as of October 18, 2022, a total of 118 cases have been reported, most of which are dominated by ages 1-5 years. This condition can occur due to impaired blood flow to the kidneys, disorders in the kidneys, or blockages in the urinary tract, with initial symptoms in the form of gastrointestinal infections and symptoms of ARI, the typical symptom is the amount of urine that decreases even can not tub at all. In such conditions, it is already an advanced phase and must be immediately taken to health facilities such as hospitals. Acute renal failure in children is a significant health problem. Its prevalence has increased in recent years and can have serious repercussions on children's health. Acute kidney failure can lead to impaired kidney function, an increased risk of complications such as edema, electrolyte disturbances and impaired body fluid balance. The process of diagnosing acute kidney failure in children can be challenging because the symptoms and signs are often nonspecific. The Diagnosis is made based on clinical evaluation, laboratory tests such as urine and blood analysis, and imaging exams if necessary. Because the knowledge and information of the community / patient is still lacking, causing delays in handling the early symptoms of acute kidney failure in children. Therefore, it is necessary to have a system in addressing the problem of acute kidney failure in children by knowing the early symptoms of the disease and other information. The system that will be built will be able to detect acute renal failure disease with symptoms suffered by patients using the dempster shafer method at the output of the system. The purpose of this study is to design an expert system application using the Dempster Shaper method in diagnosing kidney failure in children.